136-941 Mhz Lna Design For Software Defined Radio - Osman, Anwar Faizd (2014)
This research thesis describes the detailed methodology on the design of the 136- 941 mhz wideband low noise amplifier (lna) for software defined radio (sdr) base station in two-way radio applications. The operating frequencies of the design are based on the full spectrum (wideband requirement) of the tia-603c standard for land mobile fm communication equipment. The lna design process includes a comprehensive circuit analysis, design methodology and performance comparisons of the two wideband topologies selected for this research, the negative feedback technique and balanced amplifier topology. This research thesis also illustrates the simultaneous amplifier requirements in wideband application and proposed a structured practical design approach which utilizes the cad simulations in optimizing the amplifiers to meet all the required specs, to balance the design tradeoff and the drawing of the pcb layouts. The design process also includes the method of achieving accurate correlation between the simulation and the actual design. The final stage of the research process was the fabrication of the two topologies using rogers r04003c pcb board and the practical testing measurement of the design using rf equipment to verify the performance of the designed lna.